Pengembangan LKPD Berbasis Filsafat Materi Trigonometri untuk Mengetahui Kemampuan Berpikir Kritis (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Learning trigonometry always become one thing that uninterested for some senior high school student. In fact, trigonometry is an important to learn because it is one of support material for math in university. In learning proses we need a learning module that able to show student critical thinking process. The right module that fit to our purpose is Student’s Worksheet.Method that used is in preliminary prototype (self-review, expert review, one to one, small group, and field test). Three important aspects in philosophy used as main component to every activity there is ontology, epistemology, and axiology. The types of data taken is qualitative data and quantitative data. The result of this research is a philosophybased Student’s Worksheet that valid and practical for student critical thinking process.
Keywords: Mathematical Philosophy; Student’s Worksheet; Trigonometry; Critical Thinking